1987
DOI: 10.1128/mcb.7.11.4058
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific activity of the pro-opiomelanocortin gene promoter.

Abstract: The pro-opiomelanocortin (POMC) gene is specifically expressed in corticotroph cells of the anterior pituitary. To define the POMC promoter sequences responsible for tissue-specific expression, we assessed POMC promoter activity by gene transfer into POMC-expressing pituitary tumor cells and fibroblast L cells. The rat POMC promoter was only efficiently utilized and correctly transcribed in AtT-20 cells. 5'-End deletion analysis revealed two promoter regions required for activity in AtT-20 cells. When tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 46 publications
4
64
1
Order By: Relevance
“…Here, we found that CRH stimulated the rat POMC promoter K480/C63 construct, while pCPT-cAMP stimulated the rat POMC promoter K480/C63 construct to a large degree. This result coincides with those of previous reports (Jeannotte et al 1987, Ray et al 1996, Kovalovsky et al 2002, Mynard et al 2004. The low promoter activation of CRH treatment might be due to low cAMP generation, because there are some reports that described low and transient cAMP accumulation on CRH stimulation in AtT-20 cells (Litvin et al 1984, Nikodemova et al 2003.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Here, we found that CRH stimulated the rat POMC promoter K480/C63 construct, while pCPT-cAMP stimulated the rat POMC promoter K480/C63 construct to a large degree. This result coincides with those of previous reports (Jeannotte et al 1987, Ray et al 1996, Kovalovsky et al 2002, Mynard et al 2004. The low promoter activation of CRH treatment might be due to low cAMP generation, because there are some reports that described low and transient cAMP accumulation on CRH stimulation in AtT-20 cells (Litvin et al 1984, Nikodemova et al 2003.…”
Section: Discussionsupporting
confidence: 83%
“…The rat POMC promoter K480/C63 construct is sufficient for corticotroph-specific POMC expression (Jeannotte et al 1987, Hammer et al 1990, and is activated by CRH and cAMP stimulation (Kovalovsky et al 2002). Here, we found that CRH stimulated the rat POMC promoter K480/C63 construct, while pCPT-cAMP stimulated the rat POMC promoter K480/C63 construct to a large degree.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The activity of the POMC gene promoter in the pituitary context has been extensively studied both in the murine corticotroph cell line AtT-20 and in transgenic mice models (Hammer et al, 1990;Jeannotte et al, 1987;Tremblay et al, 1988). Multiple cis-regulatory elements have been identi®ed whose coordinate activities were required for POMC gene transcription (Therrien and Drouin, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The early studies of POMC 5′-flanking sequences indicated that these sequences exhibit cell-specific activity in cell culture experiments (Jeannotte et al 1987) and most importantly that they are sufficient to recapitulate to a large extent the unique features of POMC transcriptional regulation in transgenic mice (Tremblay et al 1988, Hammer et al 1990. Further, the transgenic data indicate that 480 bp upstream of the rat gene transcription start site (TSS) contained most of the critical targets for POMC regulation, notwithstanding the possibility that other regulatory sequences may also contribute to control of POMC transcription.…”
Section: Mechanisms For Pituitary Expression Of the Pomc Genementioning
confidence: 99%